Numerical Shape Optimization of Cervical Spine Disc Prosthesis Prodisc-C - Amadji, Moussa; Ameddah, Hacene; Mazouz, Hammoudi (Journal of Biomimetics, Biomaterials and Biomedical Engineering, 2018)
Various ball and socket-type designs of cervical artificial discs are in use or under investigation. All these disc designs claim to restore the normal kinematics of the cervical spine. In this study, we are interested in the cervical prosthesis, which concerns the most sensitive part of the human body, given the movements generated by the head. The goal of this work is to minimize the constraints by numerical shape optimization in the prodisc-C cervical spine prosthesis in order to improve performance and bio-functionality as well as patient relief. Prodisc-C cervical spine prosthesis consists of two cobalt chromium alloy plates and a fixed nucleus. Ultra-high molecular weight polyethylene, on each plate there is a keel to stabilize the prosthesis; this prosthesis allows thee degrees of freedom in rotation. To achieve this goal, a static study was carried out to determine the constraint concentrations on the different components of the prosthesis. Based on the biomechanical behaviour of the spine discs, we totally fixed the lower metal plate; a vertical load of 73.6 N to simulate the weight of the head was applied to the superior metallic endplate. After a static study on this prosthesis, using a finite element model, we noticed that the concentration of the Von-Mises stress is concentrated on the peripheral edge core and the concave articulating surface of the superior metallic endplate the numerical. We use the module optimization for 3D SolidWorks for optimize our design, based on the criteria of minimizing stress value. Shape optimization concluded to minimize the equivalent stress value on both joint surface (concave and convex) from 11.3 MPa to 9.1MPa corresponding to a percentage decrease of 19.4% from the original geometry. We conclude that despite the fact that maximum Von Mises stresses are higher in the case of the dynamic load, remains that they are weak. Which is an advantage for the durability of the prosthesis and-also for the bone, because a low stress concentration on the prosthesis will reduce stress concentration generated by the implant on the bone, therefore its risk of fracture reduces.